Analysis of The Alignment Between Chemistry Content on TIMSS And Science-Chemistry Textbooks of Junior High School - Oktariani, Oktariani; Febliza, Asyti (JPI (Jurnal Pendidikan Indonesia), 2019)
This study is conducted to: (1) analyze the level of alignment between chemistry content on TIMSS with science-chemistry textbooks of Junior High School and (2) describe the discrepancies between chemistry content on TIMSS with science-chemistry textbooks of Junior High School in term of cognitive demands as well as subject content covered. This study was descriptive which used content analysis method. The content analysis was conducted on chemistry content of TIMSS and science-chemistry textbooks of Junior High School. To determine the degree of alignment criteria, this study used the method developed by Porter. Accordingly, the level of alignment is symbolized by Porter's Alignment Index. The results showed that the degree of alignment between TIMSS and and science-chemistry textbooks of Junior High School was 0.49 (low level of alignment). This imperfect alignment level is characterized by the discrepancies in term of subject content covered and cognitive demands among chemistry content on TIMSS and and science-chemistry textbooks of Junior High School. This can affect certainly toward the achievement of Indonesian students in TIMSS